The History Angkringan and the Process of the Spread of Prembe from the Village of Ngerangan, Bayat, Klaten - Muhammad Ariyan Hidayat; Bagas Narendra Parahita; Nurhadi . (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this study is to describe the history of the origins of angkringan from Ngerangan Village as well as the adaptation strategy of traders in the process of spreading angkringan. The research method used is a qualitative research method. This research was conducted in Ngerangan village, Bayat sub-district, Klaten district. Data collection was done through interviews and observation. The results showed that the emergence of angkringan for the first time originated from Ngerangan Village and began its expansion to Surakarta. There is a special term that refers to someone who works as an angkringan seller, namely prembe. The process of spreading angkringan is highly dependent on the family's decision to continue the tradition of selling angkringan. Some of the adaptation strategies carried out by prembe are group life, building relationships and networking between traders, opening with local food menus, and designing the angkringan concept which is not just a place to eat, but functions as a public space that has egalitarian norms.